Binding and Transport Properties of a Benzo[b]thiophene‐Based Mono‐(thio)urea Library. Issue 3 (22nd January 2022) - Moiteiro, Cristina; Marques, Igor; Ryder, William G.; Cachatra, Vasco; Carvalho, Sílvia; Chen, Li‐Jun; Goodfellow, Brian J.; Gale, Philip A.; Félix, Vítor
Abstract: Using the chemical versatility of the benzo[ b ]thiophene motif, an extensive library of 24 (thio)urea receptors, with different binding properties and lipophilicities, was prepared and included α, α‐, α, β‐, β, β‐, β, γ‐, α, γ‐, and γ, γ‐benzo[ b ]thiophene positional isomers, as well as β‐ or γ‐benzo[ b ]thiophene‐based molecules decorated with aliphatic chains or aryl moieties with different fluorination degrees. 1 H NMR titrations, X‐ray crystallographic studies, and DFT calculations were used to study the chloride binding affinities between receptors and substrates. Experimental efflux studies suggested that the anion transmembrane transport activity is dependent on the receptors′ lipophilicity and hydrogen bonding ability. Moreover, LUV based assays indicated that anion efflux occurs mainly through an uniport mechanism. Further MD simulations showed that anion transport is highly dependent on the orientation and interactions of the receptors at the water/lipid interface. Abstract : Playing with benzo[ b ]thiophene‐based motifs as Lego bricks, an extensive library of small drug‐like synthetic receptors was designed. Their anion binding and transmembrane transport properties were investigated by a combination of experimental and theoretical approaches. The most active transporters recognize chloride using an urea assisted by a C−H binding unit from a single β‐ or γ‐benzo[ b ]thiophene motif.